2011
DOI: 10.2134/agronj2011.0115
|View full text |Cite
|
Sign up to set email alerts
|

Common Bean Seed Complements Molybdenum Uptake by Plants from Soil

Abstract: Molybdenum (Mo) reserve in large seeds can complement Mo uptake by plants from soil, but the content of Mo in common bean (Phaseolus vulgaris L.) seed for this purpose is unknown. We hypothesized that 3.639 ± 0.751 μg Mo seed -1 would be suffi cient to complement Mo uptake by irrigated common bean plants from a Mo-poor soil. Th ree fi eld experiments were performed in a clayey Ultisol naturally infested by native strains of Rhizobium in Zona da Mata, Minas Gerais, Brazil. Treatments were arranged as 4 × 2 fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 23 publications
5
29
0
2
Order By: Relevance
“…One low-cost strategy to solve this problem would be to provide farmers with Mo-rich seeds. Studies on the common bean have confirmed the efficacy of this approach (Vieira, Salgado, & Ferreira, 2005;Vieira, Paula Júnior, & Pires, 2011;Pacheco, Brito, Straliotto, Pérez, & Araújo, 2012;Almeida, Araújo, & Alves, 2013). Reducing the Mo fertilizer dose to produce Mo-rich seed can be achieved by determining the most appropriate growth stage at which to apply the fertilizer.…”
Section: Introductionmentioning
confidence: 95%
“…One low-cost strategy to solve this problem would be to provide farmers with Mo-rich seeds. Studies on the common bean have confirmed the efficacy of this approach (Vieira, Salgado, & Ferreira, 2005;Vieira, Paula Júnior, & Pires, 2011;Pacheco, Brito, Straliotto, Pérez, & Araújo, 2012;Almeida, Araújo, & Alves, 2013). Reducing the Mo fertilizer dose to produce Mo-rich seed can be achieved by determining the most appropriate growth stage at which to apply the fertilizer.…”
Section: Introductionmentioning
confidence: 95%
“…These high values of SMoCc compared to those obtained when no Mo . The horizontal dotted line represents the seed Mo content (3.6 µg) at which common bean does not respond to Mo fertilization (Vieira et al, 2011b). Thin bars represent the standard deviation.…”
Section: Mo Concentration and Content In The Seeds Of Mo-fertilized Gmentioning
confidence: 99%
“…In regions with Mo-poor soils, as in Zona da Mata, plants grown from common bean seeds containing 3.6 ± 0.7 µg Mo per seed or more (high Mo content) did not respond to Mo spraying, unlike seeds with low Mo content (Vieira et al, 2011b). Seeds with high Mo content were derived from plants sprayed with 1,000 g ha -1 Mo and those with low Mo content (0.007 ± 0.001 or 0.248 ± 0.057 µg Mo per seed) from plants sprayed with water or 90 g ha -1 Mo, respectively .…”
Section: Introductionmentioning
confidence: 97%
“…Esses méto-dos são usados por agricultores bem informados e em regiões onde há disponibilidade de adubo molíbdico no comércio. Recentemente, com o aprimoramento da téc-nica para enriquecer sementes com Mo (Vieira et al, 2005, Vieira et al, 2011Pacheco et al, 2012), é possí-vel fornecer aos agricultores, a baixo custo (Vieira et al, 2011), esse micronutriente, por meio da semente. Nesse caso, a disponibilização de Mo para a planta independe de a tecnologia ser conhecida, ou não, pelo agricultor, e de o adubo molíbdico estar disponível, ou não, no comércio local.…”
Section: Introductionunclassified
“…Na Zona da Mata, 600 g ha -1 de Mo geralmente elevam o conteúdo de Mo para pelo menos 3,6 µg por semente (Vieira et al, 2014), teor com que os feijoeiros não mais respondem à aplicação de Mo na folhagem ( Vieira et al, 2011). Nessa região, o conteú-do de Mo da semente de feijão quase dobrou quando a dose de 1440 g ha -1 de Mo foi dividida em quatro subdoses e aplicada entre V4 (terceira folha trifoliolada) e R5 (pré-floração), em comparação com o efeito da aplicação única em V4 (Vieira et al 2005).…”
Section: Introductionunclassified